Comparative Outcomes between Off-Clamp and On-Clamp Nephron-Sparing Surgery – A Retrospective Analysis (The Insight, 2025)
Objective: To compare perioperative and functional outcomes between off-clamp and on-clamp techniques during nephron-sparing surgery (NSS). Methods & Materials: A retrospective study of 70 patients who underwent NSS for renal tumors between January 2020 and July 2025. Patients were divided into two groups: Off-Clamp NSS (Group A, n=34) and On-Clamp NSS (Group B, n=36). Data on operative time, estimated blood loss (EBL), warm ischemia time (WIT), complications, and renal functional outcomes (eGFR changes) were analyzed. Results: Group A showed significantly higher EBL (p=0.02) but better postoperative renal function preservation (mean eGFR drop: 5.6% vs 11.4%, p
Keywords: Partial nephrectomy; Off-clamp technique; On-clamp technique; Nephron-sparing surgery; Warm ischemia; Estimated blood loss; Renal function preservation; eGFR decline; Positive surgical margin; Perioperative outcomes